1999
DOI: 10.1007/s10434-999-0442-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lymphatic Mapping, Sentinel Lymphadenectomy, and Selective Complete Lymph Node Dissection as a Therapeutic Procedure for Early-Stage Melanoma

Abstract: These findings suggest that LM/SL/SCLND is therapeutically equivalent to ELND but may be more effective for identifying nodal metastases in patients with intermediate-thickness primary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
2
8

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(89 citation statements)
references
References 36 publications
6
73
2
8
Order By: Relevance
“…Furthermore, previous studies involving melanomas from all anatomic sites showed a statistically significant improvement in survival in patient with intermediate thickness melanomas (range, 1-4 mm), which suggests that some subgroups of patients may benefit from ELND 3,25,31 . Finally, despite the fact that sentinel lymph node biopsy (SLNB) has been adopted into clinical practice as reliable staging modality, there are lots of arguments against it, such as increased incidence of nodal (regional and in-transit) recurrence in sentinel lymph nodes (SLN) negative patients, possibility of false-negative results, difficult identification of SLN if they are located close to primary site, SLN found in multiple node fields in contrast to melanomas located on extremities which usually drain to only 1 field, SLN in parotid region which are often very small, may be difficult to find, and their removal may put the facial nerve at risk 8,10,12,15,16,29,36,37 . However, some authors reported that intraparotid SLN biopsy is a reliable, accurate, and safe procedure for staging cutaneous head and neck melanoma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies involving melanomas from all anatomic sites showed a statistically significant improvement in survival in patient with intermediate thickness melanomas (range, 1-4 mm), which suggests that some subgroups of patients may benefit from ELND 3,25,31 . Finally, despite the fact that sentinel lymph node biopsy (SLNB) has been adopted into clinical practice as reliable staging modality, there are lots of arguments against it, such as increased incidence of nodal (regional and in-transit) recurrence in sentinel lymph nodes (SLN) negative patients, possibility of false-negative results, difficult identification of SLN if they are located close to primary site, SLN found in multiple node fields in contrast to melanomas located on extremities which usually drain to only 1 field, SLN in parotid region which are often very small, may be difficult to find, and their removal may put the facial nerve at risk 8,10,12,15,16,29,36,37 . However, some authors reported that intraparotid SLN biopsy is a reliable, accurate, and safe procedure for staging cutaneous head and neck melanoma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…3,8,[20][21][22][23][24][25] Technical failures may occur as a result of errors in lymphatic mapping and sentinel lymphadenectomy or because of a deficiency in the process of histopathologic evaluation. With long-term follow-up of patients with negative sentinel nodes there is a small but definite incidence of recurrence in the mapped and sampled nodal basin.…”
Section: Discussionmentioning
confidence: 99%
“…3,[20][21][22][23][24][25] The procedure of sentinel node biopsy at the Sydney Melanoma Unit involves preoperative injection of a technetium-99m-labelled antimony trisulfide colloid for lymphoscintigraphy, and intraoperative injection of Patent Blue V dye (Guerbert, Aulney-Sous-Bois, France) at the primary melanoma site for visual identification of sentinel nodes. Because the blue dye does not survive the processing procedures necessary for histopathologic examination and because all the technetium99m has decayed by the time that sample is ready for analysis, these features cannot be used retrospectively to confirm that a 'true' sentinel node has been removed.…”
mentioning
confidence: 99%
“…With regard to disease frees urvival (DFS) andoverall survival (OS),nosignificantd ifferencew as observedb etween pa-tients havingu ndergone immediate complete resection of lymph nodeso ft he primaryb asina nd patients whofirsth ad surgicalresection andanalysisofthe SLNfollowedb ys econdary electivel ymph node dissection in case of positivity (4).…”
Section: Introductionmentioning
confidence: 99%
“…andthe Groupe Mélanome Lémanique Departments of 1 Nuclear Medicine, 2 Dermatology, 3 Pathology, 4 Surgery,University Hospital (HUG), Geneva, Departments of 5 Surgery, 6 Nuclear Medicine, 7 Dermatology, 8 Pathology, 9 Multidisciplinary Oncology Center, University Hospital (CHUV), Lausanne, 10 Ludwig Institute for CancerResearch, UniversityofLausanne, 11 DepartmentofNuclear Medicine,Fribourg Hospital,Switzerland…”
mentioning
confidence: 99%